NPK NUTRIENT ANALYSIS OF PALM OIL WASTE - Selfa Dwie Andini Br. Tarigan; Yuan Gideon Sinaga; Tuty Ningsih; Tiffany Zia; Eka Bobby Febrianto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims (1) to make liquid organic fertilizer from fruit, vegetable and midrib waste (2) to determine the best composition and nutrient content in liquid organic fertilizer (3) to determine the effect of adding oil palm fronds to liquid organic fertilizer. This study used a non-factorial completely randomized design (CRD) method consisting of 3 treatments with 3 replications, so that the total sample was 9 samples. The parameters observed were the nutrient levels of N, P, and K fertilizers contained in the POC. The data obtained were analyzed statistically by analysis of variance (ANOVA). The results showed that the administration of oil palm midrib bone extract had no effect on all observation indicators.